Efektivitas Media Pembelajaran Berbasis Teknologi dalam Meningkatkan Pemahaman Konsep Matematika Siswa SMA - Rahmawati, Fitriana; Kirana, Arinta Rara; Partasiwi, Nurashri (STKIP PGRI Bandar Lampung, 2024)
This study aims to investigate the effectiveness of the use of technology-based learning media, including mobile applications, learning videos, and software such as GeoGebra and Matlab, in improving the understanding of mathematical concepts of high school students. Through a quantitative approach, with an experimental design, this study involved 90 students from SMA 8 Bandar Lampung who were divided into 3 groups. Data analysis was carried out using t-test to compare the level of understanding of students before and after the use of learning media. The results showed that there was a significant improvement in students' understanding of mathematical concepts after the use of technology-based learning media (p < 0.05). GeoGebra was shown to provide the best results with an increase in understanding by 48.5%, followed by mobile applications (40.2%) and learning videos (30.1%). These findings indicate that the use of technology-based learning media is effective in improving students' understanding of mathematical concepts.